Serum LAG-3 Predicts Outcome and Treatment Response in Hepatocellular Carcinoma Patients With Transarterial Chemoembolization - Guo, Mengzhou; Qi, Feng; Rao, Qianwen; Sun, Jialei; Du, Xiaojing; Qi, Zhuoran; Yang, Biwei; Xia, Jinglin (Frontiers in Immunology, 2021)
Background：Transarterial chemoembolization (TACE) stands for the most commonly utilized therapy for hepatocellular carcinoma (HCC) worldwide. This study was to explore the potential predictive and prognostic roles of LAG-3 and PD-L1 as serum biomarkers in HCC patients underwent TACE treatment. Methods：A total of 100 HCC patients receiving TACE as well as 30 healthy controls were enrolled in the study. Serum LAG-3 and PD-L1 levels were determined at baseline and 3 day after TACE using enzyme-linked immunosorbent assay (ELISA). Results：We found serum levels of LAG-3 and PD-L1 were significantly elevated in HCC patients compared with healthy controls. Interestingly, patients with low pre-TACE and post-TACE levels of LAG-3 but not PD-L1 had a high probability of achieving an objective response (OR) after TACE treatment. Additionally, high pre-TACE LAG-3 level was correlated with poor disease outcome, and the patients with both high serum LAG-3 and PD-L1 level had the shorter overall survival (OS) than patients who are either PD-L1 or LAG-3 high or both low PD-L1 and LAG-3 level. High pre-TACE serum LAG-3 level was positively associated with more cirrhosis pattern, advanced BCLC stage, pre-TACE alanine aminotransferase (ALT) level, and pre-TACE aspartate aminotransferase (AST) level. Furthermore, in 50 patients who underwent TACE, the serum LAG-3 level was significantly decreased 3 day after TACE. Conclusion: Both pre-TACE and post-TACE serum LAG-3 levels could serve as powerful predictors for tumor response of TACE, and high pre-TACE serum LAG-3 level was an indicator for poor prognosis in HCC.